2011
DOI: 10.1038/labinvest.2011.117
|View full text |Cite
|
Sign up to set email alerts
|

Claudin-4 overexpression is associated with epigenetic derepression in gastric carcinoma

Abstract: The tight junction (TJ) protein claudin-4 is aberrantly upregulated in gastric cancer, but its clinical significance and the molecular mechanisms underlying claudin-4 overexpression in gastric cancer remain unclear. Here, we investigated its roles and epigenetic mechanisms regulating CLDN4 expression in gastric cancer. We show that increased membranous expression of claudin-4 in gastric carcinoma is associated with better patient prognosis, whereas cytoplasmic claudin-4 expression did not show a significant as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 44 publications
(72 reference statements)
3
56
0
Order By: Relevance
“…However, expression of claudin-3 and claudin-4 was significantly weaker for cases with positive lymphatic invasion. It is suggested that claudin-3 and claudin-4 may be involved as important proteins during the lymphatic invasion process in gastric cancer, which is consistent with the results obtained by Jung et al(2011) for both claudins, and also those of Kwon et al (2011), who found a significant inverse correlation of claudin-4 expression with tumor invasion and metastasis. Relatively few studies have examined the expression levels of claudin-3 and claudin-4 in precursor lesions.…”
Section: Discussionsupporting
confidence: 88%
“…However, expression of claudin-3 and claudin-4 was significantly weaker for cases with positive lymphatic invasion. It is suggested that claudin-3 and claudin-4 may be involved as important proteins during the lymphatic invasion process in gastric cancer, which is consistent with the results obtained by Jung et al(2011) for both claudins, and also those of Kwon et al (2011), who found a significant inverse correlation of claudin-4 expression with tumor invasion and metastasis. Relatively few studies have examined the expression levels of claudin-3 and claudin-4 in precursor lesions.…”
Section: Discussionsupporting
confidence: 88%
“…Increased expression of CLDN4 on the membrane enhances the barrier like function of tight junctions which tends to prevent the migration and invasion of gastric cancer cells, without affecting cell growth. The epigenetic regulation of CLDN4 overexpression and its clinical significance as potential therapeutic targets was reported by Kwon et al [19] . DNA hypomethylation parallels to CLDN4 upregulation in both cancerous and non-cancerous gastric tissues.…”
Section: Chromatin Remodeling and Epigenetic Modifications As Etiologmentioning
confidence: 75%
“…DNA hypomethylation parallels to CLDN4 upregulation in both cancerous and non-cancerous gastric tissues. In normal gastric tissues, bivalent histone modifications often lead to repression of CLDN4 expression, whereas loss of repressive histone methylations results in upregulation of CLDN4 in gastric cancer cells [19] . Methylation level of long interspersed element-1 (LINE-1) is associated with esophagus gastric as well as colon cancer progression and prognosis [20] ; this helps in assessing tumor heterogeneity and drug efficacy for the personalized treatment of patients with gastrointestinal cancers.…”
Section: Chromatin Remodeling and Epigenetic Modifications As Etiologmentioning
confidence: 99%
“…Claudin 1,4 and 7 are important members of this Claudin protein family and their expressions show alterations in many different malignancies such as oesophageal, gastric, biliary (Usami et al, 2006;Agarwal et al, 2009;Kwon et al, 2011), ovarian (Kwon et al, 2010), endometrial (Pan et al, 2007;Knoecny et al, 2008), bladder (Boireau et al, 2007;Szekely et al, 2011) renal (Lechpammer et al, 2008), prostate (Landers et al, 2008), breast (Kominsky et al, 2003), cholangiocarcinoma (Bunthot et al, 2012) and pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%